Role of hysterosalpingography in evaluation of tubal factors and its comparison with sonosalpingography - Agrawal, Rainee; Shrivastava, Deepti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Laparoscopy is considered as the gold standard for assessment of tubal factors of infertility, although because of its invasive nature, cost and the need for anaesthesia and hospitalization, HSG seems to be a basic routine procedure for tubal factors. Currently with the availability of the ultrasonography machines with very good resolution, SSG can be simultaneously practiced with ultrasonography during day 7-9 of the menstrual cycle to assess tubal patency. Hence, the present study was designed to compare the accuracy of HSG with SSG for evaluation of tubal factor infertility. Methods: This was a prospective cross-sectional study of 100 consecutive women with primary or secondary infertility without active pelvic infection, selected from OPD of Department of Obstetrics and Gynaecology, Acharya Vinoba Bhave Rural Hospital associated with Datta Meghe Institute of Medical Sciences University, Sawangi (Meghe), Wardha over a period of two years from September 2014 to August 2016. Results: In the present study for diagnosing tubal patency SSG had sensitivity of 88.64%, specificity of 75%, positive predictive value of 96.29% and negative predictive value of 47.36% and diagnostic accuracy of 87%, while HSG had sensitivity of 94.32%, specificity of 83.33%, positive predictive value of 97.64% and negative predictive value of 66.66% and diagnostic accuracy of 93%. Conclusions: Initial assessment of tubal patency by HSG is better than SSG as an indirect, outdoor, non-invasive procedure although with minimal radiation hazards. It allows documentation of tubal patency enables detection of several tubal lesions and permits assessments of the fine intratubal architectural details as well as little uterine pathology. It will help in reducing the number of laparoscopic procedures and their related complications and health care costs for confirmation of tubal patency.